Comparative assessment of off-label and unlicensed drug prescription in neonatal intensive care: FDA versus Brazilian guidelines - Haline Tereza Matias Lima Costa; Arlan Peres Florencio; Priscilla Karilline do Vale Bezerra; Jéssica Escorel Chaves Cavalcanti; Tatiana Xavier Costa; Flavia Evelyn Medeiros Fernandes; Martins Rand Randall (Elsevier, 2021)
Introduction: Regulatory agencies are responsible for defining the use of off-label (OL) and unlicensed (UL) drug prescription in neonatal intensive care. However, these regulatory criteria may differ between agencies in different countries. The aim of this study was to establish the frequency of OL and UL drug prescription in a sample of patients in a neonatal intensive care unit applying the criteria of the Food and Drug Administration (FDA) of the United States and the Agência Nacional de Vigilância Sanitária (ANVISA) of Brazil, analysing the differences observed in the results based on the applied criteria. Methods: Prospective cohort study in neonates admitted for more than 24 h to the NICU of a teaching maternity hospital between August 2017 and July 2018. We obtained information concerning the drugs included in the analysis of OL and UL prescriptions from the DrugDex-Micromedex® and official information on pharmaceutical products in Brazil. We used the kappa correlation coefficient to assess the agreement between the FDA and ANVISA criteria. We defined disagreement as a kappa value of less than 0.200. Results: We evaluated 220 neonates admitted to the NICU and 17,421 items prescribed during the study period. We did not find a difference in the proportion of neonates in which at least 1 drug was prescribed under OL conditions applying the FDA versus the ANVISA criteria (96.4% vs. 98.6%). We found differences between the FDA and ANVISA in the OL classification based on the authorized age of use and indications for prescription, mainly in systemic antimicrobials and cardiovascular drugs. When we compared the prescribing information provided by the FDA and the ANVISA, we found that the criteria of the ANVISA were less specific. Conclusion: Off-label and unlicensed drug prescription are frequent in neonatal intensive care applying the criteria of either agency, although the FDA has established more detailed criteria in terms of the ages and indications for which prescription is authorized. Resumen: Introducción: Las agencias reguladoras son responsables de enmarcar la prescripción de fármacos en condiciones off-label (OL) y unlicensed (UL) en los cuidados intensivos neonatales. No obstante, los criterios de aprobación establecidos pueden variar entre las agencias de distintos países. El objetivo del estudio fue determinar la frecuencia de la prescripción de fármacos OL y UL en una muestra de pacientes en cuidados intensivos neonatales según los criterios establecidos por la Food and Drug Administration (FDA) de Estados Unidos y la Agência Nacional de Vigilância Sanitária (ANVISA) de Brasil, analizando las diferencias en los resultados obtenidos con los criterios de cada agencia. Métodos: Estudio prospectivo de cohortes en neonatos ingresados más de 24 horas en la unidad de cuidados intensivos neonatales (UCIN) de un hospital universitario materno infantil entre agosto de 2017 y julio de 2018. Se obtuvo información sobre los fármacos incluidos en el análisis de prescripción OL y UL de las bases de datos DrugDex-Micromedex® y de la información oficial sobre fármacos de Brasil. La concordancia entre los criterios de la FDA y de la ANVISA se evaluó por medio del índice kappa. Los valores de kappa < 0,200 se consideraron indicativos de discordancia. Resultados: Se evaluó a 220 neonatos ingresados en la UCIN y 17 421 prescripciones de fármacos individuales en el período de estudio. No hubo diferencias en la proporción de pacientes que recibieron al menos una prescripción OL según se aplicasen los criterios de la FDA o los de la ANVISA (96,4% vs. 98,6%). En cambio, se encontraron diferencias en el motivo de clasificación como OL en base a la edad o a la indicación entre las dos agencias reguladoras, principalmente en la prescripción de antiinfecciosos sistémicos y agentes cardiovasculares. Al comparar las condiciones de prescripción aprobadas por la FDA y la ANVISA, se observó que los criterios de la ANVISA eran menos específicos. Conclusiones: La prescripción de fármacos off-label y unlicensed es frecuente en los cuidados intensivos neonatales aplicando los criterios de cualquiera de las dos agencias, los criterios de la FDA son más específicos en cuanto a los grupos de edad y las indicaciones para los que se autoriza el uso de los fármacos.